THE RELATIONSHIP BETWEEN KNOWLEDGE AND SOCIAL HABITS ON THE INCIDENCE OF DIARRHEA AMONG STUDENTS IN INDRA JAYA SUB-DISTRICT, ACEH JAYA DISTRICT IN 2023 - Hikmah, Nurul; Hidayattullah, Mhd. (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
Diarrhea is a disease that is still a child health problem in Indonesia that is closely related to the food consumed. In Indonesia, elementary school students are a group that often experiences food poisoning and diarrhea due to careless snacking. To determine the relationship between knowledge and social habits with the incidence of diarrhea in students of SD Negeri 2 Indra Jaya, this study used analytical research with a descriptive design design, namely used in sampling is non probability sampling with purposive sampling technique, with a minimum sample size of 50 students. The population of this study were grade 3-5 students totaling 50 students. With a sample taken as many as 50 students. Data collection using questionnaires and data analysis using the fisher test. The results of the study obtained children who have knowledge and social habits with frequent diarrhea as many as 35 respondents. Based on the analysis of the relationship between knowledge and habits of students about diarrhea with handling actions in diarrhea, the results obtained there is a significant relationship between knowledge and social habits of students about diarrhea with handling actions in diarrhea.